Cardiac rhabdomyomas in childhood: six cases from a single institution - Kutluk, Tezer; Demir, Hacı Ahmet; Büyükpamukçu, Münevver; Ozkutlu, Süheyla; Akyüz, Canan; Varan, Ali; Yalçın, Bilgehan (The Turkish Journal of Pediatrics, 2013)
Primary cardiac tumors are rare during childhood. The most frequently encountered tumors are rhabdomyomas. We reviewed the clinical characteristics, treatment results, and outcomes of six pediatric patients with primary cardiac rhabdomyomas. The mean age was 16.8 days. Only one patient was symptomatic. The tumors mostly originated from the left ventricle. The diagnosis was established by magnetic resonance imaging (MRI) plus echocardiography with or without histopathology. Total tumor resection was performed in two patients. After a median follow-up of 39 months, one patient had a stable tumor, two patients had marked tumor regression and one had complete tumor regression. Considering the fact that rhabdomyomas often show spontaneous regression, close follow-up may be sufficient in hemodynamically stable cases. Although rhabdomyomas do not cause any symptoms at the time of diagnosis, they may lead to sudden death; thus, further studies may be required for the decision of surgery and/or followup. The localization and infiltrative characteristics of the tumor are critical factors for decision-making in children with symptomatic rhabdomyoma even if surgery is indicated in such cases.